Sulfide‐Bridged Covalent Quinoxaline Frameworks for Lithium–Organosulfide Batteries. Issue 16 (13th March 2023) - Haldar, Sattwick; Bhauriyal, Preeti; Ramuglia, Anthony R.; Khan, Arafat H.; De Kock, Sunel; Hazra, Arpan; Bon, Volodymyr; Pastoetter, Dominik L.; Kirchhoff, Sebastian; Shupletsov, Leonid; De, Ankita; Isaacs, Mark A.; et al.
Abstract: The chelating ability of quinoxaline cores and the redox activity of organosulfide bridges in layered covalent organic frameworks (COFs) offer dual active sites for reversible lithium (Li)‐storage. The designed COFs combining these properties feature disulfide and polysulfide‐bridged networks showcasing an intriguing Li‐storage mechanism, which can be considered as a lithium–organosulfide (Li–OrS) battery. The experimental–computational elucidation of three quinoxaline COFs containing systematically enhanced sulfur atoms in sulfide bridging demonstrates fast kinetics during Li interactions with the quinoxaline core. Meanwhile, bilateral covalent bonding of sulfide bridges to the quinoxaline core enables a redox‐mediated reversible cleavage of the sulfursulfur bond and the formation of covalently anchored lithium–sulfide chains or clusters during Li‐interactions, accompanied by a marked reduction of Li–polysulfide (Li–PS) dissolution into the electrolyte, a frequent drawback of lithium–sulfur (Li–S) batteries. The electrochemical behavior of model compounds mimicking the sulfide linkages of the COFs and operando Raman studies on the framework structure unravels the reversibility of the profound Li‐ion–organosulfide interactions. Thus, integrating redox‐active organic‐framework materials with covalently anchored sulfides enables a stable Li–OrS battery mechanism which shows benefits over a typical Li–S battery. Abstract : Redox activity of covalent sulfide bridging and chelating ability of quinoxaline nodes in covalent organic frameworks offer dual active sites for a novel lithium–organosulfide battery. This shows negligible polysulfide shuttle in comparison with typical sulfur cathodes in the lithium–sulfur battery. Experimental and computational elucidation indicate a reversible mechanism.